Causes of Delays of Motorable Bridge Construction Under Postal Highway Projects, Department of Roads - Suwal, Arjun; Shrestha, Santosh Kumar (Journal of Advanced College of Engineering and Management, 2016)
Successful completion of project can be linked up with timely completion of the project. This paper highlights on causes of delays in motor able bridge construction of Postal Highway Project under Department of Roads in Nepal. Out of 80 bridges under the project, 36 are completed and others are under construction. Questionnaires were distributed to 75 respondents from employers, consultants and contractors involved in Postal Highway Project. Data were analyzed based on 57 questionnaires received from questionnaire survey; interview with concerned Project Manager, Consultants, Contractors and progress reports. The main causes of delay are unusual low bid by contractors, lack of planned pre-execution of the project, delay in receiving clearances from various government authorities, poor site management and supervision by contractors due to large number of work in hand.Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 85-92